Minding the gap. Drug-related problems among breastfeeding women - Morze, Karolina; Szałek, Edyta; Waszyk-Nowaczyk, Magdalena (Frontiers in Pharmacology, 2025)
IntroductionDrug-related problems (DRPs) are a significant concern in many patient populations, including breastfeeding women. This study aimed to identify and characterize those problems in a group of breastfeeding women seeking specialized pharmaceutical care.Materials and methodsA prospective observational study was conducted among women who registered for a pharmacist’s online consultation regarding medication safety in lactation. 200 patients were enrolled. Patient medical history, medication use, breastfeeding practices, and DRPs were assessed. DRPs were classified using the Pharmaceutical Care Network Europe Association (PCNE) classification system. Causality assessment for adverse events was performed using the Naranjo algorithm and the Liverpool Causality Assessment Tool (LCAT).ResultsThis study found a high prevalence of DRPs among 190 out of 200 breastfeeding women. Of these, 27 experienced potential DRPs, and 163 manifested actual DRPs. A total of 218 DRPs were identified, with ineffective therapy being the most frequent (63.3%, n = 138). Among all identified causes (n = 265), the most common were patient-related factors (47.5%, n = 126) and dispensing-related issues, particularly regarding the information provided to patients about medication safety during lactation. Pharmacist interventions were accepted by 79.5% (n = 151) of patients, with 70% (n = 133) of DRPs successfully resolved.ConclusionThis study highlights the significant burden of DRPs among breastfeeding women and the potential for medical professionals to improve patient outcomes through evidence-based interventions. Future research should focus on developing evidence-based guidelines for medication use during lactation and improving healthcare provider education to optimize maternal and infant health.